1994
DOI: 10.1172/jci117235
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bone resorption in vitro by antisense RNA and DNA molecules targeted against carbonic anhydrase II or two subunits of vacuolar H(+)-ATPase.

Abstract: The bone resorbing cells, osteoclasts, express high levels of carbonic anhydrase II (CA II) and vacuolar H+-ATPase (VATPase) during bone resorption. We have used antisense RNA and DNA molecules targeted against CA II, and against 16-and 60-kD subunits of vacuolar H+-ATPase (V-ATPase), to block the expression of these proteins in vitro. Osteoclastic bone resorption was studied in two in vitro culture systems: release of 45Calcium from prelabeled newborn mouse calvaria cultures, and resorption pit assays perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…It has been shown that expression of the proton channel part of V-H + -ATPase is stimulated in resorbing osteoclasts (21) and that antisense RNA and DNA molecules targeted against two subunits of the V-H + -ATPase do indeed inhibit bone resorption by rat osteoclasts (22). This enzyme is therefore a major potential target for reducing osteoclast activity and, consequently, for designing novel agents useful for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that expression of the proton channel part of V-H + -ATPase is stimulated in resorbing osteoclasts (21) and that antisense RNA and DNA molecules targeted against two subunits of the V-H + -ATPase do indeed inhibit bone resorption by rat osteoclasts (22). This enzyme is therefore a major potential target for reducing osteoclast activity and, consequently, for designing novel agents useful for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…In resorbing osteoclasts, carbonic anhydrase II is highly expressed, whereas in nonresorbing osteoclasts only low basal expression is maintained. Antisense RNA targeted against carbonic anhydrase inhibits bone resorption in vitro [20].…”
Section: Osteoclast Physiologymentioning
confidence: 99%
“…For this process, carbonic anhydrase II (CA II), which is abundant in the osteoclast cytoplasm and on the inner surface of its ruffled border, catalyzes the hydration of CO 2 to bicarbonate and a proton, thereby contributing to the H + secretion acidifying the bone resorption compartment and to HCO 3 − secretion by the HCO 3 − /Cl − exchanger, which maintains pH homeostasis. (19) The blockage of CA II with antisense oligonucleotides or acetazolamide, a potent CA II inhibitor, has been reported to suppress bone resorption by osteoclasts, (20,21) and a CA II deficiency syndrome has been shown to exhibit nonfunctional osteoclasts and osteopetrosis. (22) In addition, CA II expression is stronger in actively resorbing mature osteoclasts than in nonresorbing osteoclasts.…”
mentioning
confidence: 99%